Social skills and bullying in fourth year high school students in the educational institution "Kumamoto" of the network N ° 06. Ugel 04, Puente Piedra, Lima 2017 - Gutiérrez Carrión, José Luis (2019)
We have observed with great concern our children, adolescents and young students, their fragility and lack of will, their violent inclinations in their daily school life, which causes them a series of psychological, social, cultural and family problems. It is necessary to use all the necessary and sufficient strategies to reduce the high rate of children  suffering  from  aggression  and  violence,  not  only  psychological  but  also physical violence. We must be alert to the causes of bullying. It is necessary to raise awareness among school authorities and parents, the educational community in general that children and young people should have a harmonious environment without violence where respect for others is privileged and develop a culture of peace that allows them to live in peace and develop their qualities, abilities and talents. One of the causes would be family violence, as a context that allows imitative behavior in young people. Definitely everything starts in the family, those who come from dysfunctional homes, where the treatment of parents is violent, authoritarian and disdainful and with little communication originates children who bullying their peers. Especially in adolescents who are undergoing biological and psychological changes, they should have an environment of tolerance, understanding and communication. Another possibility is the lack of development of social skills that prevents a healthy interpersonal relationship. The latter is explained by the understanding of what social skills are, which we understand as the abilities to interact with others in a social context such as schools, since, in a certain way, the adolescent is accepted or valued socially. it has as a corollary a personal benefit and, at the same time, it is mainly beneficial for others. (Combs and Slaby, 1977) In this way, knowing the levels of social skills will allow us to propose in the training areas of the curriculum that programs are inserted to optimize these social skills in students. This study will not only be useful for the students who participate in it, but also for educators, for education in its objective of forming healthy and emotionally balanced personalities that contribute to the development of their society. Another important contribution at the theoretical level is to check whether the buylling is related to social skills which is one of the factors associated with it in students. This  problem  induces  us  to  formulate the  problem  of research.  Likewise we have appreciated that these behaviors occur in secondary school populations of men and women. Behaviors that can not be stopped by teachers or as we previously pointed out that they are not understood. Considering some of them that these are normal behaviors or games of children or simply some teachers are indifferent to this violence. On the other hand, our observations as pedagogues have led us to question the possible causes, considering that social skills can and are related to the buy-down. This study aims to find the relationship between these two variables. With all of the above and with our experience in pedagogical work and tutorial guidance as tutors at the secondary level we have appreciated that our students in general present difficulties at the level of their interpersonal relationships, considering the same may be due to a lack of development of basic social skills. This has led to an investigation that allows examining social skills if the buy-in of these students is related to their social skills.